Communication media in electronic negotiations: how the individual x medium fit influences negotiation behaviors and outcomes - Lipp, Wolfram; Mohnen, Alwine (Frontiers in Communication, 2024)
Researchers and practitioners alike are interested in understanding the specifics of electronic negotiations as more and more negotiations are conducted electronically. Intuitively, we would expect differences across negotiation media, but research provides diverging results as to the impact of the medium. This research contributes to this discourse and aims to uncover differences across media and investigates the impact of individual factors on e-negotiation behavior and outcomes. While we know from previous research that individual factors influence job performance and preference for negotiation media, the impact on behaviors and outcomes in different computer-mediated negotiation media is yet to be explored. This paper proposes the individual x medium fit hypothesis, which asserts that individual factors play a distinct role in different electronic negotiation media. We tested this hypothesis using an online, mixed-motive negotiation simulation in which participants (n = 187) negotiated either in a chat or in a video conference system. The impacts of individual factors on the outcome and mediator variables were estimated with a structural equation model. We confirmed the hypothesis that individual factors have different impacts in a video and a chat negotiation: In the video negotiation, gender significantly predicted negotiation outcomes. Women used fewer words compared to men, which leads both to a lower individual profit and a better subjective value. In the chat negotiation, openness, conscientiousness, and extraversion predicted negotiation outcomes. In addition, individual factors affected attitudes toward the negotiation and behaviors. The results indicate that some individuals have an advantage in certain media. Overall, the impact of individual factors in e-negotiations seems to be limited even though such an impact is intuitively assumed by many negotiators.